Effects of Isosorbide Dinitrate on the Urinary Flow Rate in Patients With Benign Prostatic Hyperplasia - Roshani, Ali; Khosropanah, Iraj; Salehi, Mohammad; Noshad Kamran, Alireza (Urology Journal, 2010)
PURPOSE: To compare the immediate effects of a systemic nitric oxide (NO) donor with placebo on the uroflowmetric parameters in patients with benign prostatic hyperplasia (BPH). MATERIALS AND METHODS: Eighty patients with the mean age of 61.5 years (range, 49 to 74 years) who suffered from BPH were enrolled in the study. We examined peak flow rate, average flow rate, and residual urine in all the patients. Then, patients were randomized to receive either 20 mg sublingual isosorbide dinitrate (ISDN) (n = 40) or placebo (n = 40) 20 minutes prior to the second uroflowmetry, which was performed one day after the first test. RESULTS: The mean peak flow rate increased from 7.6 ± 0.41 mL/s to 10.2 ±0.54 mL/s (P = .013) in the ISDN group, while it increased +0.40 mL/s in the placebo group (P > .05). Mean residual urine volume decreased significantly from 51 ± 3.1 mL to 29 ± 2.9 mL and from 56 ± 4.1 to 51 ± 2.6 in the ISDN (P = .02) and the placebo groups (P > .05), respectively. At baseline, the mean arterial pressure was 95 ± 2.1 mmHg and under the influence of the NO-donor, it decreased to 83 ± 1.9 mmHg, which was significant (P < .001). No significant changes of micturition parameters were found in the placebo group. CONCLUSION: Organic nitrates influence micturition parameters in patients with BPH. This new approach could offer a potential pharmacological option to treat obstructive lower urinary tract symptoms.